Disseminated Mucormycosis with Positive Aspergillus Galactomannan. (24th December 2018) - Kitmiridou, Despoina; Aung, Su N.; Farmakiotis, Dimitrios
Abstract : We describe a case of disseminated mucormycosis ( Apophysomyces elegans ) diagnosed on autopsy, in a man who had been working in construction with undiagnosed neutropenia from hairy-cell leukemia, which is rarely associated with invasive mold infections. Galactomannan values in both blood and bronchoalveolar lavage were strongly positive. There is an unmet need for accurate noninvasive fungal diagnostic tests. Detailed history, including occupational exposures, can be more informative than laboratory workup.